Radioembolisation with 90Y microspheres for neuroendocrine liver metastases: an institutional case series, systematic review and meta-analysis. Issue 7 (July 2019) - Frilling, Andrea; Clift, Ashley K.; Braat, Arthur J.A.T.; Alsafi, Ali; Wasan, Harpreet S.; Al-Nahhas, Adil; Thomas, Robert; Drymousis, Panagiotis; Habib, Nagy; Tait, Paul N.
Abstract: Background: Neuroendocrine liver metastases are clinically challenging due to their frequent disseminated distribution. This study aims to present a British experience with an emerging modality, radioembolisation with yttrium-90 labelled microspheres, and embed this within a meta-analysis of response and survival outcomes. Methods: A retrospective case series of patients treated with SIR-Spheres (radiolabelled resin microspheres) was performed. Results were included in a systematic review and meta-analysis of published results with glass or resin microspheres. Objective response rate (ORR) was defined as complete or partial response. Disease control rate (DCR) was defined as complete/partial response or stable disease. Results: Twenty-four patients were identified. ORR and DCR in the institutional series was 14/24 and 21/24 at 3 months. Overall survival and progression-free survival at 3-years was 77.6% and 50.4%, respectively. There were no grade 3/4 toxicities post-procedure. A fixed-effects pooled estimate of ORR of 51% (95% CI: 47%–54%) was identified from meta-analysis of 27 studies. The fixed-effects weighted average DCR was 88% (95% CI: 85%–90%, 27 studies). Conclusion: Current data demonstrate evidence of the clinical effectiveness and safety of radioembolisation for neuroendocrine liver metastases. Prospective randomised studies to compare radioembolisation with other liver directed treatment modalities are needed.